How you live your story selected works by Kevin Jerome Everson - Everson, Kevin Jerome 1965- (Second Run, 2021)
"The American artist Kevin Jerome Everson has created a remarkable body of moving image work that co-exists within film and art exhibition contexts. With a sense of place and history, his films, shot primarily on 16mm, combine scripted and documentary moments with touches of formalism. The focus is on craft and duration, and the gestures and tasks caused by certain physical and socio-economic conditions in the lives, labour and leisure of working-class Black Americans and people of African descent. They suggest not only the relentlessness of everyday life but also reveal its inherent beauty." [secondrundvd.com
Original: USA 2005-2020
Bildformat 1.33:1, 1.78:1
Keywords: Alltag; Schwarze; USA; Film; Blu-Ray-Disc